Teknik Relaksasi Imagery Terhadap Respons Penerimaan (Psikologis dan Biologis) dalam Prosedur Invasif pada Anak Usia Sekolah (8-12 Tahun) - Nursalam Nursalam; Kristiawati Kristiawati; Yuni Sufyanti Arief; Nuzul Qur’aniati; Dyah Surya (Universitas Airlangga, 2007)
The objective of this study was to explain the effect of the imagery relaxation technique on psychological acceptance and biologic response in school age (8-12 years) on the invasive procedure. The design used in this study was static group comparison. The population was the school age patient, around 8-12 years in Melati Room RSUP Dr. Soedono Madiun. Sample of this study were 20 respondent, recruited by using purposive sampling consisting of 10 respondents as the control group and 10 respondents as the experiment group, who met the inclusion criteria. The independent variable was the imagery relaxation technique and the dependent variable was the psychological and biological acceptance responses. Data were collected by using observation paper. The result showed that there were some differences between the control group and the experiment group in heart rate (p=0.000) and the respiratory rate (p=0.000), but there were no differences in the control group`s systole (p=0.476) and diastole (p=0.630). Conclusion: the imagery relaxation technique has significantly effect on the psychological acceptance response and the biological response (the respiratory rate and the heart rate).